Políticas de expansão para o ensino superior: a implementação do REUNI na Universidade Federal de Roraima - Souto, Clivea de Farias (2017)
This dissertation aimed to analyze the implementation process of the Program of Support in Restructuring and Expansion Plans of the Federal Universities (REUNI) at the Federal University of Roraima (UFRR), in order to identify its main impact on the institution. Initially he briefly addressed the origin and history of higher education in Brazil, its influences and its developments. It dealt with reforms aimed at this level of education and its policies of expansion in the neoliberal context from the governments of Fernando Henrique Cardoso (FHC) to the administrations of Luiz Inácio Lula da Silva (Lula). He presents the documents that made up the REUNI program at national and local level, with its goals and guidelines of the documents that have subsidized its implementation at UFRR. Finally, an analysis of these documents and the statements of the subjects involved in this process was made reaching the main impacts of the program in this IFES and among them are: increased evasion, increased student teacher ratio, increased infrastructure with questionable quality, among others, where it could be noted that expansion policies serve much more to massify education than meet social needs which they propose to carry out.